Math, asked by wwwjyotiradityasizwa, 11 months ago

(C+1)(x+9) -132
 ({x + 1})(x + 9) =  {13}^{2}
(x + 1)(x + 9) =  {13}^{2}

Answers

Answered by sharmashaweta35
0

Answer:

[ tex] (X+1) ( x) +9) =13] ^[2] [ tex]

Step-by-step explanation:

hope...

Answered by LeParfait
0

Solution:

Given, (x+1)(x+9)=13^{2}

\Rightarrow x^{2}+10x+9=169

\Rightarrow x^{2}+10x-160=0

Using quadratic formula, we get

x=\frac{-10\pm\sqrt{100+640}}{2}

=\frac{-10\pm\sqrt{740}}{2}

=\frac{-10\pm 2\sqrt{185}}{2}

=-5\pm\sqrt{185}

Answer: Requires solution is

  • x=-5\pm\sqrt{185}
Similar questions